Light-responsive and transcription-enhancing elements regulate the plastid psbD core promoter. - Allison, L A (1995)
The psbD operon of higher plant plastids is regulated transcriptionally through the activity of an upstream light-responsive promoter. To identify promoter elements important for the regulation, portions of the tobacco psbD 5' region were fused to the reporter gene, uidA, and were introduced into the tobacco plastid genome by targeted gene insertion. Examination of uidA mRNA accumulation in dark-adapted and light-treated transplastomic plants revealed that a 107 bp segment of psbD 5' sequence was sufficient to promote light-responsive expression of the reporter gene in vivo. The 107 bp promoter region contains three pairs of short, repeated sequences upstream of the core promoter -10/-35 elements. Deletion of the upstream-most A-rich sequences resulted in a 5-fold decrease in reporter gene mRNA accumulation, but did not affect the light response. Additional removal of the second and third repeated elements further reduced the promoter strength approximately 30-fold and almost eliminated the light-dependent accumulation of uidA transcripts. These data indicate that the architecture of chloroplast promoters is more complex than previously assumed, and may comprise general enhancer and regulatory elements in addition to the core promoter motifs. Transcriptional regulation of psbD may be mediated by the chloroplast proteins which were shown to interact with the repeated sequences.